Navigating the Food Policy Landscape (Cha Kula Podcast - Episode 5) - Resnick, Danielle; Mockshell, Jonathan (Route to Food Initiative, 2023)
Our agri-food systems are facing unprecedented challenges, exacerbated by factors such as the COVID-19 pandemic, civil conflicts, lack of political will, poverty, inequality, power in a few hands, loss of biodiversity and climate change. These challenges go beyond the immediate need for technological solutions; they demand a nuanced understanding of the political and economic drivers that shape our food systems.